Minimally invasive single‐vessel left internal mammary to left anterior descending artery bypass grafting improves outcomes over conventional sternotomy: A single‐institution retrospective cohort study. Issue 9 (3rd July 2019) - Smith, Nathan J.; Miles, Bryan; Cain, Michael T.; Joyce, Lyle D.; Pearson, Paul; Joyce, David L.
Abstract: Background: Coronary artery bypass grafting (CABG) can be performed through a variety of approaches. Minimally‐invasive CABG (MICABG) may reduce perioperative morbidity. Previous results demonstrate improved perioperative outcomes; however, adoption has been limited. Methods: The Society of Thoracic Surgeons (STS) database and electronic medical record at a single institution were reviewed for isolated left internal mammary to left anterior descending artery (LIMA‐LAD) bypass procedures performed between 2011 and 2018. Patients were grouped on the basis of operative approach, comparing sternotomy to non‐sternotomy (minimally‐invasive). Patient characteristics, perioperative variables, and short‐ and long‐term outcomes were compared. Primary outcomes included mortality and major adverse cardiac events (MACE). Secondary outcomes were morbidity. Results: A total of 42 MICABG and 54 conventional LIMA‐LAD procedures were performed with 95.2% of MICABG procedures performed by two surgeons. MICABG were more often elective (83.3 vs 38.9%, P  < .001). STS risk scores predicted equitable mortality and morbidity for MICABG dependent on operative indication. MICABG was associated with fewer pulmonary complications (0.0 vs 11.1%, P  = .033), in‐hospital events (11.9 vs 37.0%, P  = .005), and shorter intensive care unit (34.1 vs 66.0 hours, P  = .022) and total length of stay (3.7 vs 6.5 days, P  = .002). There were no observed strokes, myocardial infarctions, or reoperations. MICABG patients demonstrated reduced thirty‐day mortality (0.0 vs 10.9%, P  = .036) and improved Kaplan‐Meier 5‐year (95.2 vs 77.9%, P  = .016) and MACE‐free survival (89.2 vs 63.9%, P  = .010). Conclusions: Minimally‐invasive LIMA‐LAD CABG demonstrates improved early postoperative morbidity and a long‐term mortality benefit. In select patients, minimally‐invasive approaches to single‐vessel grafting may be beneficial when performed by experienced surgeons in the elective setting.